Theories and models used on articles published by the Public Health Journal of the National University of Colombia, 1999-2004 - Gustavo A. Cabrera A (Universidad de Antioquia, 2008)
Objective: to identify the main features of the theories and theoretical models used in the articles published by the Revista de Salud Pública (Public Health Journal) of the National University of Colombia. Methods: in February 2005 all the numbers published by the journal from 1999 to 2004 were analyzed. A trained reader registered different variables of interest based on instruments and criteria adapted from previous studies. Results: A total amount of six volumes corresponding to 21 numbers of the journal were read, 18 of the periodical publication and 3 special numbers. A total amount of 154 contributions were classified into 66 articles or research summaries (43%), 62 essays, revisions or conferences on specific topics (40%), and 26 on up-to-date subjects or symposia (17%). The main topics were health system and policies (26%), epidemiology (21%) and health management (13%). Although 34 of 154 articles (22%) referred to 9 theories and 39 models as theoretical frameworks, only 17 (11%) involve a deep usage of them according to the criteria adopted. Conclusions: the articles published in the journal revealed a limited use of theories and models and a lack of rigor in the way the authors structured them from the point of view of subject, methodology and analysis.